2012
DOI: 10.1257/aer.102.1.576
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Shrouded Fees: Evidence from a Natural Experiment in the Indian Mutual Funds Market

Abstract: We study a natural experiment in the Indian mutual funds sector that created a 22-month period in which closed-end funds were allowed to charge an arguably shrouded fee, whereas open-end funds were forced to charge entry loads. Forty-five new closed-end funds were started during this period, collecting $7.6 billion US, whereas only two closed-end funds were started in the 66 months prior to this period, collecting $42 billion US, and no closed-end funds were started in the 20 months after this period. We estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(44 citation statements)
references
References 9 publications
3
41
0
Order By: Relevance
“…Second, our results show that price promotions have attention effects that can backfire from the promoter's perspective, thereby adding evidence to literatures on the psychology of incentives (Gneezy and Rustichini (), Kamenica ()) and price changes (Hastings and Shapiro ()) that have not yet focused much on shrouded prices. Our results are consistent with findings from other domains suggesting that consumers respond differently to base prices and add‐on prices (Chetty, Looney, and Kroft (), Brown, Hossain, and Morgan (), Anagol and Kim ()) . Lastly, our results are consistent with predictions from “transaction utility” models in which perceptions of fairness, not merely absolute value of a product or service, influence willingness‐to‐pay (e.g., see Thaler ()).…”
supporting
confidence: 92%
“…Second, our results show that price promotions have attention effects that can backfire from the promoter's perspective, thereby adding evidence to literatures on the psychology of incentives (Gneezy and Rustichini (), Kamenica ()) and price changes (Hastings and Shapiro ()) that have not yet focused much on shrouded prices. Our results are consistent with findings from other domains suggesting that consumers respond differently to base prices and add‐on prices (Chetty, Looney, and Kroft (), Brown, Hossain, and Morgan (), Anagol and Kim ()) . Lastly, our results are consistent with predictions from “transaction utility” models in which perceptions of fairness, not merely absolute value of a product or service, influence willingness‐to‐pay (e.g., see Thaler ()).…”
supporting
confidence: 92%
“…5 The first seminal work on US mutual fund industry was by Jensen in 1968 where he showed that MF managers, on average, don't outperform the market net of fees and expenses. 6 See, for example, Anagol and Kim (2012). (1989,1993), Wermers (1999Wermers ( , 2000, and Chen, Jegadeesh, and Wermers (2000)) that use holdings-based performance measures find evidence suggesting that fund managers possess superior ability.…”
Section: Mutual Fund Performance and Fund Manager Abilitymentioning
confidence: 99%
“…During this time the …nancial sector has become much larger and more sophisticated, but remains highly regulated, with a signi…cantly nationalized banking sector. Recently, authors such as Anagol and Kim (2012) have begun to study Indian …nancial regulation and its impacts on fast-changing Indian capital markets.…”
Section: Introductionmentioning
confidence: 99%